(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This research aims to analyze grammatical problems faced by the seventh semester students of STKIP Abdi Pendidikan Payakumbuh in writing introduction chapter of research proposal. The research also determines the caused of those problems. 50 students involved in the study. The study showed that the students had grammatical problems in writing introduction chapter of research proposal, exactly in tenses 293 problems (37.66%). The caused of students’ grammatical problems is overgeneralization. Dealing with the way of lecturer teaching grammar, it was found that the grammar lecturer strategy was still inappropriate. Thus, it is suggested to English lecturer to use various teaching strategies in teaching grammar to make the students master grammar before starting writing.